Exceptional children and youth : an introduction to special education - Hunt, Nancy; Marshall, Kathleen (Boston : Houghton Mifflin, 1994)
Building blocks for working with exceptional children. Learning about the potential of exceptional children. Considering cultural diversity and lifespan factors.
Keywords: Education; Special education